Asymptotics for the Solutions to Defective Renewal Equations - Kaiyong Wang; Yang Chen; Zhongquan Tan (Abstract and Applied Analysis)
This paper investigates the defective renewal equations under the nonconvolution equivalent distribution class. The asymptotics of the solution to the defective renewal equations have been given for the heavy-tailed and light-tailed cases, respectively.